(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article examines the syntactic meaning of one - partedness, defines the semantic features of sentences with one main member. The signs of impersonal sentences are characterized in detail: semantic basis, structural features. The main types of impersonal sentences are described taking into account the general meaning and morphological nature of the main term. The classification of structural and semantic groups of impersonal constructions takes into account the grammatical form of mandatory and optional members. The presented classification shows that the meaning of impersonal sentences receives a different structural expression. However, in all structural variants there is a common element – a form of impersonality with the same indicators.